2022
DOI: 10.3390/ijms23179833
|View full text |Cite
|
Sign up to set email alerts
|

Role of Citrullinated Collagen in Autoimmune Arthritis

Abstract: Citrullination of proteins plays an important role in protein function and it has recently become clear that citrullinated proteins play a role in immune responses. In this study we examined how citrullinated collagen, an extracellular matrix protein, affects T-cell function during the development of autoimmune arthritis. Using an HLA-DR1 transgenic mouse model of rheumatoid arthritis, mice were treated intraperitoneally with either native type I collagen (CI), citrullinated CI (cit-CI), or phosphate buffered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Interestingly, gelatin, which is a mixture of peptides and proteins produced by the partial hydrolysis of collagen consists of small collagen fragments and also has the capacity to bind LAIR-1 but not to activate it. We previously found that LAIR-1 binding to trimeric collagen peptides is influenced by glycine-proline-hydroxyproline (GPO) content of collagen, and recently it was shown that citrullinated collagen binds LAIR-1, but does not signal, resulting in inactive LAIR-1 44 , although other factors contribute to the interaction as well 18,29 . In addition, we identified a collagen peptide (II-17) that binds to LAIR-1 but is unable to induce LAIR-1 signaling 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, gelatin, which is a mixture of peptides and proteins produced by the partial hydrolysis of collagen consists of small collagen fragments and also has the capacity to bind LAIR-1 but not to activate it. We previously found that LAIR-1 binding to trimeric collagen peptides is influenced by glycine-proline-hydroxyproline (GPO) content of collagen, and recently it was shown that citrullinated collagen binds LAIR-1, but does not signal, resulting in inactive LAIR-1 44 , although other factors contribute to the interaction as well 18,29 . In addition, we identified a collagen peptide (II-17) that binds to LAIR-1 but is unable to induce LAIR-1 signaling 29 .…”
Section: Discussionmentioning
confidence: 99%
“…PAD4 is mainly produced by neutrophils and deletion of this enzyme in mouse tumor models, results in lower neutrophil infiltration in tumors and reduced tumor progression [ 114 ]. In Rheumatoid arthritis citrullinated collagen can bind LAIR-1 as decoy ligand impairing the immunosuppressive function of LAIR-1 on T cells [ 115 ]. In cancer, impaired LAIR-1 mediated inhibition could lead to inflammation in inappropriate sites, depending on the citrullinated collagen location within the tumor.…”
Section: Collagen Post-translational Modifications and Their Impact O...mentioning
confidence: 99%
“…These results lead to the hypothesis that the citrullination of joint collagen determines a specific pattern of interaction with different cell types, potentially favoring the binding of cells with proinflammatory properties and preventing cartilage localization and the survival of mesenchymal stem cells with immunosuppressive and anti-inflammatory potential. Another role of COL2 citrullination in RA that involves interactions with the leukocyte-associated immunoglobulin such as receptor 1 (LAIR-1; CD305) has recently been demonstrated [ 117 ]. Collagens are natural ligands for LAIR-1, which, when activated, have the potential to inhibit inflammatory responses and contribute to the maintenance of immune homeostasis [ 118 ].…”
Section: Collagen Type II (Col2) Posttranslational Modifications In R...mentioning
confidence: 99%
“…Collagens are natural ligands for LAIR-1, which, when activated, have the potential to inhibit inflammatory responses and contribute to the maintenance of immune homeostasis [ 118 ]. Interestingly, Myers et al have demonstrated that the PAD4-mediated citrullination of COL2 induces the antagonistic effect of the protein regarding its interaction with LAIR-1 [ 117 ]. Supported by the proven expression of PAD2 and PAD4 in RA synovia [ 119 ], these findings suggest that in arthritic joints, citrullinated COL2 could inhibit the LAIR-1-mediated downregulation of autoimmune responses, and thus, perpetuate the disease.…”
Section: Collagen Type II (Col2) Posttranslational Modifications In R...mentioning
confidence: 99%